Examining External Support Received in Prison and Concerns About Reentry Among Incarcerated Women. (April 2016) - Mancini, Christina; Baker, Thomas; Sainju, Karla Dhungana; Golden, Kristin; Bedard, Laura E.; Gertz, Marc
Few studies have examined whether social ties influence concerns about reentry among women in prison. Given that a systematic understanding of reentry has the potential to inform research and policy efforts to assist women with transition, this gap is limiting. Our study addresses this void by testing whether social support affects reentry concerns (family, employment, financial, and stigma) among incarcerated women. Results indicate that visits reduced all concerns; receiving letters had a less consistent effect, but they too, were associated with reduced worry. In addition, experiencing multiple types of support influenced reentry concerns among women. Research and policy implications are discussed.